2019
DOI: 10.1002/adma.201902181
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Methanol‐to‐Olefins (MTO) Catalysts

Abstract: Among the 8-MR molecular sieves, silicoaluminophosphate SAPO-34 with 3D channels and moderate acid strength represents the most interesting one, the light olefins selectivity of which could reach up to 90% or even higher. [7] The excellent MTO performance of SAPO-34 was first reported by Dalian Institute of Chemical Physics (DICP) in 1990. [8] The researchers also demonstrated the good regeneration stability and high-temperature steam stability of Inspired by these pioneering discoveries, extensive research e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
198
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(201 citation statements)
references
References 122 publications
(89 reference statements)
3
198
0
Order By: Relevance
“…By use of mimics of the HCPs as organic structure-directing agents (OSDAs) to synthesize CHA and RTH-related zeolites, it is possible to maximize the host–guest interaction between framework and polymethyl aromatic intermediates to promote the propylene/ethylene ratio 8 , 11 . However, precise design and synthesis of targeted zeolites with specific OSDAs are extremely challenging 23 , especially the HCPs slightly different in structures may significantly change the product selectivity 8 . Co-feeding of methanol with organic intermediates, e.g., alkenes 24 , aromatics 25 or formaldehyde 26 , has also been applied to adjust ethylene/propylene ratio via altering the HCPs dominating either olefinic or aromatic cycle 2 , 6 according to dual-cycle mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…By use of mimics of the HCPs as organic structure-directing agents (OSDAs) to synthesize CHA and RTH-related zeolites, it is possible to maximize the host–guest interaction between framework and polymethyl aromatic intermediates to promote the propylene/ethylene ratio 8 , 11 . However, precise design and synthesis of targeted zeolites with specific OSDAs are extremely challenging 23 , especially the HCPs slightly different in structures may significantly change the product selectivity 8 . Co-feeding of methanol with organic intermediates, e.g., alkenes 24 , aromatics 25 or formaldehyde 26 , has also been applied to adjust ethylene/propylene ratio via altering the HCPs dominating either olefinic or aromatic cycle 2 , 6 according to dual-cycle mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…For the SP34-RS and SP34-AS X samples, both high-and low-temperature peaks were less intense than those of SP34, which suggested the decreasing trend of acid site density in these samples. It is well known that SAPO-34 catalysts with mild acid strength and relatively low acid site density are more appropriate for the MTO reaction [5] . The catalytic activities of the six samples in the MTO reaction were evaluated in a fixed bed reactor at 400 ℃ with a methanol WHSV of 2.0 h -1 , and the results were plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Zeolites with uniform micropores, tunable acidities, and high thermal/hydrothermal stability are important heterogeneous acidic catalysts in the petrochemical and fine chemical industries [1][2][3] . In recent years, as a successful alternative route of producing light olefins via a nonpetrochemical approach from the abundant resources of coal, natural gas, and even biomass, the zeolitecatalyzed methanol-to-olefins (MTO) reaction has gained considerable attention from academic and industrial communities [4][5][6][7][8] . After extensive experimentation using various molecular sieves, it was demonstrated that smallpore 8-membered ring (8-MR) molecular sieves served as excellent catalysts in the MTO reaction (100% methanol conversion) [9] .…”
mentioning
confidence: 99%
“…Inorganic open-framework metal phosphates have been widely studied due to their channel structure and potential applications in industrial catalysis, gas separations, and so forth [1][2][3][4]. For example, SAPO-34 catalysts provide an alternative platform for methanol conversion to olefins (MTO), which produces basic chemicals from nonparallel resources, such as natural gas and coal [5]. Since the aluminophosphate zeolite was first reported in 1982 [6], various metal phosphate materials have been found in related literature [7][8][9].…”
Section: Introductionmentioning
confidence: 99%